2004
DOI: 10.1016/s0896-6273(04)00155-2
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Discrimination of Unperceived Objects during Binocular Rivalry

Abstract: Rapid identification of behaviorally relevant objects is important for survival. In humans, the neural computations for visually discriminating complex objects involve inferior temporal cortex (IT). However, less detailed but faster form processing may also occur in a phylogenetically older subcortical visual system that terminates in the amygdala. We used binocular rivalry to present stimuli without conscious awareness, thereby eliminating the IT object representation and isolating subcortical visual input to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
234
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(261 citation statements)
references
References 66 publications
22
234
3
2
Order By: Relevance
“…Other lesion studies have reported amygdala responsivity towards fearful or fear conditioned faces when presented in subjects' blind field (Morris et al, 2001) and during visual extinction (Vuilleumier et al, 2002). Neuroimaging studies have found similar results in amygdala activity using psychophysical techniques that manipulate subjects' awareness, including visual masking (Whalen, 1998;Whalen et al, 2004;Williams et al, 2006, but see Pessoa et al, 2006Phillips et al, 2004), and binocular rivalry (Pasley et al, 2004;Williams et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Other lesion studies have reported amygdala responsivity towards fearful or fear conditioned faces when presented in subjects' blind field (Morris et al, 2001) and during visual extinction (Vuilleumier et al, 2002). Neuroimaging studies have found similar results in amygdala activity using psychophysical techniques that manipulate subjects' awareness, including visual masking (Whalen, 1998;Whalen et al, 2004;Williams et al, 2006, but see Pessoa et al, 2006Phillips et al, 2004), and binocular rivalry (Pasley et al, 2004;Williams et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…By contrast, the major cortical pathway relaying visual input to the amygdala does not show substantial activity and functional connectivity under the same conditions but does so during conscious perception of emotional stimuli (Pasley, Mayes, & Schultz, 2004;Williams et al, 2006). Not surprisingly, similar findings have been reported in patients with affective blindsight in response to unseen facial and bodily expressions and indicate that a functional subcortical pathway to the amygdala is engaged during nonconscious emotion perception (de Gelder et al, 2005;Morris et al, 2001;Pegna et al, 2005;Van den Stock et al, 2011.…”
Section: Functional and Structural Neuroanatomymentioning
confidence: 81%
“…LeDoux (1994) proposed a dual-route model through which the amygdala receives input on emotional salience: a coarse but rapid subcortical input directly from the thalamus, and slower routes from cortical sensory areas. Beyond extensive findings from the animal literature, support for the rapid subcortical pathway in humans comes from numerous neuroimaging studies using facial expressions (Morris et al, 1999;Pasley et al, 2004;Reinders et al, 2006). reported decreased response time to fear-relevant stimuli (snakes and spiders) versus fearirrelevant stimuli (flowers and mushrooms) in a visual search task administered to healthy college students.…”
Section: Methodsmentioning
confidence: 99%
“…It is critically involved in the detection of, and learning about, emotionally relevant stimuli, including events that have high social salience such as recognizing the meaning of facial expressions (Pasley et al, 2004;Vuilleumier & Pourtois, 2007). The "amygdala theory" of autism (Baron-Cohen et al, 2000; see also Bachevalier, 1996;Howard et al, 2000;Schultz et al, 2003) proposes that atypical social development in autism may arise from primary dysfunction in the amygdala and related "social brain" structures (Brothers, 1996;Skuse et al, 2003).…”
Section: Introductionmentioning
confidence: 99%